Optics and Photonics as a strong and resilient field for a successful career development - Kress, Bernard (Photonics Letters of Poland, 2023)
When compared to other enabling technology fields such as Electronic Engineering or Computer Science, Optics and Photonics stands out to be by far the oldest field of research, and yet the one still standing today at the forefront of research, consumer electronics, transformation industry, communication, health, biotech and many more. From solving the mysteries of our universe to the development of the latest smart phones and the fastest internet lines, the field of Optics and Photonics has proven over and over to be at the cornerstone for everything we take for granted today. This field has been associated with many successive market booms, and sometimes also bubbles, but the underlying technology build by its exceptional engineers never gets wasted or lost, providing valuable key building blocks to fuel the “next big thing” Full Text: PDF References https://money.cnn.com/2001/12/18/technology/q_yearend_telecom DirecLink https://money.cnn.com/2010/11/09/technology/jdsu_qualcomm/index.htm DirectLink https://www.forbes.com/global/1999/1129/098_01.html?sh=290252831d0c DirectLink B. Kress, Applied Digital Optics: From Micro-optics to Nanophotonics (John Wiley 2007). DirectLink K. Curtis, D. Psaltis, "Cross talk in phase-coded holographic memories", J Opt Soc Am. 10(12), 2547 (1993). CrossRef W.S. Colburn, B.J. Chang, "Holographic combiners for head up displays", Tech Report No. AFAL-TR-77-110, (1977). DirectLink J. Kimmel, T. Levola, P. Saarikko, "A novel diffractive backlight concept for mobile displays", J Soc Inf Disp 16(2), (2008). CrossRef